Allergic diseases and the effect of inhaled epinephrine in children with acute bronchiolitis: follow-up from the randomised, controlled, double-blind, Bronchiolitis ALL trial. Issue 9 (September 2015) - Skjerven, Håvard Ove; Rolfsjord, Leif Bjarte; Berents, Teresa Løvold; Engen, Hanne; Dizdarevic, Edin; Midgaard, Cathrine; Kvenshagen, Bente; Aas, Marianne Hanneborg; Hunderi, Jon Olav Gjengstø; Stensby Bains, Karen Eline; Mowinckel, Petter; Carlsen, Kai-Håkon; et al.
Summary: Background: Although use of inhaled bronchodilators in infants with acute bronchiolitis is not supported by evidence-based guidelines, it is often justified by the belief in a subgroup effect in individuals developing atopic disease. We aimed to assess if inhaled epinephrine during acute bronchiolitis in infancy would benefit patients with later recurrent bronchial obstruction, atopic eczema, or allergic sensitisation. Methods: In the randomised, double-blind, multicentre Bronchiolitis ALL trial, 404 infants with moderate-to-severe acute bronchiolitis were recruited from eight hospitals in Norway to receive either inhaled epinephrine or saline up to every second hour throughout the hospital stay. Randomisation was done centrally, and the two study medications (20 mg/mL racemic epinephrine or 0·9% saline) were prepared in identical bottles. The dose given depended on the infant's weight: 0·10 mL, less than 5 kg; 0·15 mL, 5–6·9 kg; 0·2 mL, 7–9·9 kg; and 0·25 mL, 10 kg or more; all dissolved in 2 mL of 0·9% saline before nebulisation. The primary outcome was the length of hospital stay. In this follow-up study, 294 children were reinvestigated at 2 years of age with an interview, a clinical examination, and a skin prick test for 17 allergens, determining bronchial obstruction, atopic eczema, and allergic sensitisation, on which subgroup analyses were done. Analyses were done by intention to treat. The trial has been completed and is registered atClinicalTrials.gov (numberNCT00817466 ) and EUDRACT (number 2009-012667-34). Findings: Length of stay did not differ between patients who received inhaled epinephrine versus saline in the subgroup of infants who developed recurrent bronchial obstruction by age 2 years (143 [48.6%] of 294 patients; pinteraction =0·40). However, the presence of atopic eczema or allergic sensitisation by the age of 2 years (n=77) significantly interacted with the treatment effect of inhaled epinephrine (pinteraction =0·02); the length of stay (mean 80·3 h, 95% CI 72·8–87·9) was significantly shorter in patients receiving inhaled epinephrine versus saline in patients without allergic sensitisation or atopic eczema by 2 years (−19·9 h, −33·1 to −6·3; p=0·003). No significant differences were found in length of hospital stay in response to epinephrine or saline in children with atopic eczema or allergic sensitisation by 2 years (+16·2 h, −11·0 to 43·3; p=0·24). Interpretation: Contrary to our hypothesis, hospital length of stay for bronchiolitis was not reduced by administration of inhaled epinephrine in infants who subsequently developed atopic eczema, allergic sensitisation, or recurrent bronchial obstruction. The present study does not support an individual trial of inhaled epinephrine in acute bronchiolitis in children with increased risk of allergic diseases. Funding: Medicines for Children Network, Norway.